2014
DOI: 10.1111/apa.12810
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of thinness from birth to early childhood: the association with parental thinness

Abstract: Careful observation of body weight from birth is important to reduce thinness at 5 years of age. Paternal thinness may be a risk factor for thinness in boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The presence of maternal overweight and obesity during childhood has been reported as a risk factor for child obesity [39,[65][66][67]. In this context, the present study also showed that maternal overweight/obesity at their child's pre-adolescence was associated with high odds of child and adolescent obesity, second to those found for the pre-pregnancy.…”
Section: Discussionsupporting
confidence: 71%
“…The presence of maternal overweight and obesity during childhood has been reported as a risk factor for child obesity [39,[65][66][67]. In this context, the present study also showed that maternal overweight/obesity at their child's pre-adolescence was associated with high odds of child and adolescent obesity, second to those found for the pre-pregnancy.…”
Section: Discussionsupporting
confidence: 71%
“…Their birth weight was required to be ≥2.5 kg and <4.0 kg. The details of these participants and the method of data collection are available elsewhere [21].…”
Section: Normal Birth Weight Controlsmentioning
confidence: 99%
“…Analysis of the effect size showed only a small effect size for sex. The values of anthropological parameters of younger school age were presented in other countries, e.g., from Africa (Nigeria) [17,18]; from South America (Brazil) [38,40]; from Taiwan [11]; from India [31,57]; from Malaysia [9]; from Ireland [42]; from Japan [29,30,39]; and from Turkey [27].…”
Section: Discussionmentioning
confidence: 99%
“…During the ontogeny of an individual, changes in body structure occur depending on sex, populations, and ethnic groups [1,3,4,5,8,18,20,24,38,40,44,45,46,48,50,52,56]. Therefore, reference charts are necessary for pediatric monitoring of child growth and development [9,11,29,30]. Based on anthropometric measurements, monitoring and evaluation of healthy development and performance of children in the Czech Republic and Slovakia were also carried out [7, 12, 25 35].…”
Section: Introductionmentioning
confidence: 99%